De-novo Domestication for Improving Salt Tolerance in Crops - Razzaq, Ali; Saleem, Fozia; Wani, Shabir Hussain; Abdelmohsen, Shaimaa A. M.; Alyousef, Haifa A.; Abdelbacki, Ashraf M. M.; Alkallas, Fatemah H.; Tamam, Nissren; Elansary, Hosam O. (Frontiers in Plant Science, 2021)
Global agriculture production is under serious threat from rapidly increasing population and adverse climate changes. To ensure food security is currently a huge challenge to feed 10 billion people by 2050. Climate changes deteriorating the natural ecosystem and increased the spells of various abiotic stresses. Salinity tolerance is one of the most prevailing stress that currently posing severe damage to crop yield on large scale. Traditional domestication is not good enough to fast-track the crop production as it causes genetic erosion during intensive selection and eliminate unique stress-responsive genes. Recent innovations in state-of-the-art genomics and transcriptomics technologies have paved the way for de novo domestication to produce superior new crop genotypes. De novo domestication exploited crop wild relatives (CWRs) to retrieve the lost genetic diversity of a species and reintroduced tolerant-genes from wild to new crops. Next-generation sequencing (NGS) open new avenues in identifying the unique genes from the CWRs. This has also led to the assemble of highly annotated crop pan-genomes to snapshot the full landscape of genetic diversity and recapture the huge gene repertoire of a species that has been lost during domestication. The identification of novel salt tolerance genes alongside the emergence of cutting-edge genome editing tools for targeted manipulation renders de novo domestication a way forward for developing climate-ready future crops.